2019
DOI: 10.1002/dmrr.3108
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of breastfeed in women with prior gestational diabetes mellitus: A systematic review and meta‐analysis

Abstract: Summary This study was undertaken to provide comprehensive analyses of current research developments in the field of breastfeed (BF) and metabolic‐related outcomes among women with prior gestational diabetes mellitus (GDM). Database PubMed, Embase, BIOSIS Previews, Web of Science, and Cochrane Library were searched through December 3, 2017. Odds ratio (OR) and weighted mean difference (WMD) with 95% confidence interval (CI) were pooled by random‐effects model using Stata version 12.0. Twenty‐three o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 64 publications
(225 reference statements)
1
19
0
Order By: Relevance
“…Compared with women with shorter duration of BF, longer BF duration was associated with improvement in glucometabolic parameters, including lower fasting glucose and enhanced insulin sensitivity, lower BMI at follow up improved lipid metabolism as demonstrated by lower triglyceride levels. Thus, BF is potentially of great value as a low cost preventative measure in preventing both T2DM and related metabolic derangements in women with a history of GDM, in addition to its other well recognized benefits ( 80 ). Evidence for prevention of CV disease in women with history of GDM through post-partum interventions is currently lacking; but logically breast feeding and improved post-partum lifestyle would be predicted to reduce the risk significantly.…”
Section: Prevention Of Future Ncd—mother and Offspringmentioning
confidence: 99%
“…Compared with women with shorter duration of BF, longer BF duration was associated with improvement in glucometabolic parameters, including lower fasting glucose and enhanced insulin sensitivity, lower BMI at follow up improved lipid metabolism as demonstrated by lower triglyceride levels. Thus, BF is potentially of great value as a low cost preventative measure in preventing both T2DM and related metabolic derangements in women with a history of GDM, in addition to its other well recognized benefits ( 80 ). Evidence for prevention of CV disease in women with history of GDM through post-partum interventions is currently lacking; but logically breast feeding and improved post-partum lifestyle would be predicted to reduce the risk significantly.…”
Section: Prevention Of Future Ncd—mother and Offspringmentioning
confidence: 99%
“…Tanase-Nakao et al (2017) reported that longer lactation (more than 4 and up to 12 weeks) of any intensity reduced diabetes risk compared to the shorter-lactation group [ 35 ]. Moreover, Ma et al reported positive effects from long-term breastfeeding of any intensity to reduce the risk of dysglycemia in women after GDM pregnancy, particularly in long-term follow-up studies [ 36 ]. However, the studies included in the analyses were primarily conducted in Western populations [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…GDM is associated with significant maternal and fetal morbidities. Mothers with GDM are at increased risks of preeclampsia, polyhydramnios, preterm birth, and cesarean delivery, while fetal and neonatal complications include macrosomia, shoulder dystocia, neonatal jaundice, and hypoglycemia [ 2 ]. Studies have shown that rising maternal glucose leads to a graded increase in the risk of complications, even within the accepted normal plasma glucose range [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The documented prevalence of GDM worldwide varied substantially from 1% to more than 30%. The lack of universally accepted screening and diagnostic criteria for GDM has made international comparisons difficult [ 2 ]. Various international bodies, including the World Health Organization (WHO), advocate screening all pregnant women for diabetes, while the British National Institute for Health and Care Excellence (NICE) supports risk-based screening [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation